The Impact of Global Extremism on Canada: Addressing the Local Threat - Mubin Shaikh (The Journal of Intelligence, Conflict and Warfare)
On May 15, 2025, Mr. Mubin Shaikh presented “The Impact of Global Extremism on Canada: Addressing the Local Threat” for the CASIS Vancouver May 2025 Digital Roundtable. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were the ways in which foreign conflicts are influencing extremism within Canada, and how current mitigation efforts remain insufficient given the speed and scope of online radicalization and disinformation.